A REVIEW ON MOBILE ELECTRONIC WASTE RECYCLING AMONG MALAYSIAN USERS - Chin, Tay Lee; Chee, Tay Lee (Graduate Program of Universitas Tarumanagara, 2025)
The increase of electronic gadgets and appliances has led to a higher amount of mobile electronic waste (e-waste). Despite that, the awareness among Malaysian users regarding mobile e-waste recycling remains deficient. Our reviews clearly show that users’ awareness on mobile e-waste recycling is to assess their understanding and knowledge level based on the Knowledge, Attitudes and Practices (KAP) model proposed by Schwartz (1976). Further, mobile e-waste recycling intention and motivation is closely linked to an individual’s environmental mindset, incentive strategies, environmental education, convenience and disposal cost. Additionally, Malaysian Communications and Multimedia Commission (MCMC) and Non-Government Organizations (NGOs) have introduced various methods, platforms and practices on mobile e-waste recycling. There is no clear review of mobile e-waste recycling among Malaysian users, driving this study conducts a review of Malaysian users’ awareness and perception, intention, motivations, methods and platforms on mobile e-waste recycling. This study helps the policy makers to enhance information dissemination of mobile e-waste and support Sustainable Development Goals (SDGs) namely clean water and sanitation (goal 6), sustainable cities and communities (goal 11), responsible production and consumption (goal 12). This study helps to detect the limitations of the Malaysian users on advancing awareness for more sustainable mobile e-waste recycling.